Combining ability and heterosis analysis in linseed (Linum usitatissimum L.) - Kumar, Sanjiv; Kerkhi, S.A.; Kumar, Anuj; Singh, S D (Annals of Agricultural Research, 2014)
The present study was conducted in ten varieties/parental lines of linseed (Linum usitatissimum L.) The study suggested that both additive and non additive components of genetic variation were Â important in the expression of most of the traits. For breeding better varieties the promising parents viz. Parwati, Padmini, Shekhar, J- 23 and T-397 which are having high GCA effects in desirable direction may be incorporated as parent in crossing programme to have better genotype for yield and its components. The manifestation of high degree of heterosis in certain cross combinations viz. Himalini Ã— Heera and Parwati Ã— Himalini indicated great possibility of developing hybrids for commercial cultivation.